2010
DOI: 10.2135/cropsci2009.04.0173
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Mapping of Complex Turfgrass Sites: Site‐Specific Management Units and Protocols

Abstract: Site‐specific management units (SSMUs), similar in soil, plant, and irrigation requirements, are foundational to efficient management in precision agriculture. This concept is applied to management of complex turfgrass sites to improve irrigation practices. An experimental mobile unit mapped two golf fairways' turfgrass (Paspalum vaginatum SW.; ‘Salam’) in Naples, FL in summer 2006 on a 2.5 m grid for volumetric water content (VWC) by time‐domain reflectrometry at field capacity and normalized difference veget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 31 publications
2
35
0
Order By: Relevance
“…Mobile platforms to obtain both spatial and temporal soil and plant data rapidly over large areas of turfgrass for routine mapping were not available until 2005 when the first experimental unit was developed; namely the Toro mobile multi-sensor (TMM) unit (The Toro Company, Bloomington, MN; patent pending) (Krum et al 2010). This device, described in more detail later, can determine VWC (%) by TDR, turfgrass performance by NDVI, compaction by penetrometer resistance (kg cm -2 ) and record position with GPS.…”
Section: Multi-sensor Mobile Platformsmentioning
confidence: 99%
See 4 more Smart Citations
“…Mobile platforms to obtain both spatial and temporal soil and plant data rapidly over large areas of turfgrass for routine mapping were not available until 2005 when the first experimental unit was developed; namely the Toro mobile multi-sensor (TMM) unit (The Toro Company, Bloomington, MN; patent pending) (Krum et al 2010). This device, described in more detail later, can determine VWC (%) by TDR, turfgrass performance by NDVI, compaction by penetrometer resistance (kg cm -2 ) and record position with GPS.…”
Section: Multi-sensor Mobile Platformsmentioning
confidence: 99%
“…• Statistical and geostatistical analyses by appropriate methods. Corwin and Lesch (2005b) and Taylor et al (2007) suggested statistical and geostatistical methods to determine SSMUs for agriculture sites, while Krum et al (2010) suggested methods to define SSMUs for turfgrass situations. • Geographical information systems (GIS) database development and graphical display.…”
Section: Protocolsmentioning
confidence: 99%
See 3 more Smart Citations